Estado de la periurbanización en Francia: el caso de Nancy - De Miguel González, Rafael (Geographicalia, 2017)
The aim of this article is showing, how the process of periurbanization has been developed in Nancy and also, the management actions for the territorial shaping. The author describes the general tendences in France, which urban system Nancy is placed in. Finally, morphological and fonctional analyses of Nancy's rural-urban fringe are exposed in conexion with the hole of the urban aglomeration.
Keywords: Periurban management; lotisseinent; zane d'avlénagement concerté; activity area; daily migrations; urbanisation front